The business case for resilient agriculture: A financial and risk analysis of maize farming technologies in Kenya - Nowak, Andreea C.; Steward, Peter R.; Namoi, Nictor; Kamau, Hannah N.; Lamanna, Christine; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Maize-mixed farming is the most important food production system in East and Southern Africa, stretching over 19% of the cultivated area and engaging approximately 60 million people [1]. In Kenya, maize (Zea mays L.) is the main staple of 96% of the population and is cultivated by more than a third (38%) of the farmers [2]. Roughly 70% of production is small-scale (0.1-2 hectares [ha]) [3]. Maize areas cover approximately 1.8 million ha, from the coast lowlands (1-1250 meters above the sea level [masl]) to high potential highlands (>2100 masl), including eight provinces: Rift Valley (with the largest area under maize), Nyanza, Eastern, Western, Coast, Central, North Eastern, and Nairobi.